Bevölkerungs- und sozialgeographische Untersuchung als Grundlage der Sanierungs- und Sozialplanung. Ein Beitrag zur angewandten Geographie - Killisch, W.F.; Moch, K.-J. (ERDKUNDE, 1976)
The study is concerned with the use of population- and social geographic investigations for social planning in the context of urban renewal projects. The study was performed in three residential districts in the old part of Lübeck, close to the CBD. It is based mainly on a series of inter views relating to 368 households in those districts. The first part of the study is an extensive description of the spatial and social structure and an evaluation of the renewal needs of the districts. A summary of the results provides further suggestions for a social plan and for further renewal projects; a discussion of the consequences related to those measures completes the study.